Optimizing phenytoin therapy: a systematic review of clinically relevant food and herb interactions - Orellana-Paucar, Adriana Monserrath; Mosquera-Lopez, Erick Thomas; Bustamante-Alvarez, Nancy Michelle; Machado-Orellana, María Gabriela; Vintimilla-Rojas, Daniela Alejandra; Atiencia-Palacios, John Diego; Espinoza-Fajardo, Ana Cristina (Frontiers in Pharmacology, 2026)
IntroductionPhenytoin, a widely prescribed anticonvulsant, presents clinical challenges due to its narrow therapeutic index and potential interactions with various foods, herbs, and medications. These interactions can lead to adverse effects or subtherapeutic responses, necessitating a thorough understanding by healthcare professionals to optimize patient care.MethodsThis systematic review investigates clinically significant interactions between phenytoin and dietary components. A comprehensive search across PubMed, Scopus, and the Health Virtual Library identified relevant studies published from January 1960 to December 2024. Data extraction utilized standardized forms, and evidence certainty was evaluated using the GRADE criteria.ResultsTwelve of the 826 initially identified articles met the inclusion criteria. Findings revealed diverse interactions: three articles reported no interaction, five indicated enhanced drug absorption, and one noted improved drug effectiveness. Conversely, three studies documented reduced efficacy due to interactions with specific foods or herbs.DiscussionThe review suggests that co-administration of phenytoin with folic acid may prevent deficiency without affecting plasma concentrations or drug efficacy. Concurrent use of phenytoin and piperine should be monitored due to potential absorption and increases in plasma levels. Additionally, it is suggested that the combination of noni and phenytoin be avoided, as it may reduce phenytoin concentrations to subtherapeutic levels. While these findings are based on studies of moderate evidence quality, further controlled clinical trials are necessary to refine pharmacological recommendations.Systematic Review RegistrationCRD42018117308.